2021
DOI: 10.1111/1541-4337.12862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the consumption of guarana on human health: A narrative review

Abstract: Guarana (Paullinia cupana) is a plant from the Amazon region with cultural importance. Despite its early ancestral use by indigenous tribes, the first reports regarding the benefits of guarana consumption for human health were published in the 19th century. Since then, the use of guarana seed in powder and extract forms has been studied for its diverse effects on human health, such as stimulating, anti-inflammatory, antioxidant, anticancer, hypocholesterolemic, and antiobesity effects. These effects are attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 139 publications
(239 reference statements)
0
18
0
1
Order By: Relevance
“…Comparatively, lesser but still substantial evidence also exists for the ability of these compounds to exert some antioxidant actions in vivo. In fact, a number of studies in humans and animals have revealed that the increase in several markers of biological oxidation induced by ROS, such as F2-isoprostanes, hydroperoxyoctadecadienoic acids, 8-hydroxy-2′-deoxyguanosin, oxidized low density lipoprotein, nitrotyrosine and other nitrosylated or carbonylated amino acids and proteins, can be effectively prevented or ameliorated by the ingestion of certain flavonoid-rich plant foods or the administration of either flavonoid-rich extracts or pure flavonoids, as reviewed by several authors [ 46 , 47 , 48 , 49 ]. The broad recognition of the latter effects of flavonoids is likely to account for the so generalized and long perception that “flavonoids act primarily as antioxidant molecules”.…”
Section: Flavonoids As Antioxidantsmentioning
confidence: 99%
“…Comparatively, lesser but still substantial evidence also exists for the ability of these compounds to exert some antioxidant actions in vivo. In fact, a number of studies in humans and animals have revealed that the increase in several markers of biological oxidation induced by ROS, such as F2-isoprostanes, hydroperoxyoctadecadienoic acids, 8-hydroxy-2′-deoxyguanosin, oxidized low density lipoprotein, nitrotyrosine and other nitrosylated or carbonylated amino acids and proteins, can be effectively prevented or ameliorated by the ingestion of certain flavonoid-rich plant foods or the administration of either flavonoid-rich extracts or pure flavonoids, as reviewed by several authors [ 46 , 47 , 48 , 49 ]. The broad recognition of the latter effects of flavonoids is likely to account for the so generalized and long perception that “flavonoids act primarily as antioxidant molecules”.…”
Section: Flavonoids As Antioxidantsmentioning
confidence: 99%
“…When compared to controls, patients with pulmonary tuberculosis who received a combination of catechins and antituberculosis showed a significant increase in blood levels of reduced glutathione, an antioxidant effect that plays an important role in the human oxidative stress mechanisms ( 68 ). In addition, the levels of ROS metabolites such as F2-isoprostaglandins are considerably reduced when flavonoids are consumed over time ( 69 , 70 ).…”
Section: Effect Of Flavonoids To Promote Scar-free Regenerationmentioning
confidence: 99%
“…Hodiernamente pesquisadores confirmaram os benefícios associados ao consumo das sementes de guaraná vão além das propriedades estimulantes ocasionadas pelos altos teores de cafeína (Schimpl, Silva, Gonçalves, & Mazzafera, 2013).pois essas sementes também possuem polifenóis com diversos benefícios na suplementação humana. Altos teores de metilxantinas e flavonóides presentes nessa espécie são biodisponíveis e contribuem para reduzir o estresse oxidativo de indivíduos por ação antioxidante com efeitos estimulantes, anti-inflamatórios, anticancerígenos, hipocolesterolêmicos e antiobesidade (Torres et al, 2022).…”
Section: Introductionunclassified